Indonesian EFL students’ views on their explicit and implicit language aptitude profiles, TOEFL scores and language proficiency. - Kartini Tobroni; Farah Natchiar; Wan Mazlini (Journal of English Education and Teaching, 2021)
This study is designed to find out students’ views on their explicit and implicit language aptitude profiles, TOEFL scores and language proficiency. Based on purposive sampling scheme, the data were collected from sixty-five students in the end of their eighth semester at the English department in faculty of teacher training in UIN Raden Fatah Palembang. The students were asked to respond to the five points Likert scale questionnaire which consists of four parts: Part A elicits the participants’ demographic information, Part B on language experience, Part C on language aptitude, and Part D especially on TOEFL and language proficiency.  The findings revealed that language learning success is attributed to a number of individual factors. The individual factors related to foreign language learning can be divided into affective factors (e.g., motivation, attitude, and personality) and cognitive factors (e.g., intelligence, aptitude). The cognitive factors interact with affective factors for learning a particular language which may explain why a person is better able to learn a language over another language. Thus, a full model of language learning that considers the impact of language aptitude on learning should also investigate the combined mediating role of individual differences such as motivation, anxiety, and learner’s beliefs.